2022
DOI: 10.3389/fmed.2022.995019
|View full text |Cite
|
Sign up to set email alerts
|

Potential tolerability of ancient grains in non-celiac wheat sensitivity patients: A preliminary evaluation

Abstract: Background and aimsA wheat-free diet (WFD) represents the elective treatment for Non-celiac Wheat Sensitivity (NCWS) patients. Preliminary reports have shown a possible better tolerability of ancient grains in these subjects. The aim of this observational study was to evaluate the frequency of consumption of ancient grains and its correlation with clinical manifestations in NCWS patients.Methods223 NCWS patients were recruited, and their consumption of ancient grains was monitored. Participants were first admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Probiotics have been shown to be an excellent source of endopeptidases, which can reduce gluten content in wheat foods and seem to be the strongest candidates for improving the quality of gluten-free foods [42]. In this regard, it has been reported that "ancient" wheats, which partially differ in composition from "modern" wheat species, seem to be better tolerated (lower rate of symptom onset, better palatability, and lower cost than gluten-free products) by a subset of NCWS patients [56,57]. As Bifidobacteria and Lactobacilli strains are known to be the most common probiotics used in foods and supplements, we evaluated the effect of a probiotic mix containing B. longum, L. acidophilous, A 4 h fermentation with these probiotics considerably decreased IL-17A (p = 0.001) and IFN-γ (p = 0.003), increased IL-10 (p < 0.0001) and TGF-β (p < 0.0001), and reduced (not statistically significant) IL-6 (p > 0.05) mRNA levels compared to the non-fermented dough-extracted PT-gliadin-incubated Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been shown to be an excellent source of endopeptidases, which can reduce gluten content in wheat foods and seem to be the strongest candidates for improving the quality of gluten-free foods [42]. In this regard, it has been reported that "ancient" wheats, which partially differ in composition from "modern" wheat species, seem to be better tolerated (lower rate of symptom onset, better palatability, and lower cost than gluten-free products) by a subset of NCWS patients [56,57]. As Bifidobacteria and Lactobacilli strains are known to be the most common probiotics used in foods and supplements, we evaluated the effect of a probiotic mix containing B. longum, L. acidophilous, A 4 h fermentation with these probiotics considerably decreased IL-17A (p = 0.001) and IFN-γ (p = 0.003), increased IL-10 (p < 0.0001) and TGF-β (p < 0.0001), and reduced (not statistically significant) IL-6 (p > 0.05) mRNA levels compared to the non-fermented dough-extracted PT-gliadin-incubated Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these modern techniques are extrusion, microwave, ohmic heating, ultrasound, 3D printing and high-pressure processing [11,12,44]. Sprouting/germination and high-pressure processing have been used to reduce the antinutrients and improve the organoleptic properties of the ancient grains, and high-pressure processed ancient grains with reduced antinutrients and improved organoleptic properties have been successfully produced and used in the production of various foods such as pasta and bread [13,15,80]. There is also a growing interest in isolating different functional components from ancient grains, such as starch, protein, bran and fibre, oil and bioactive compounds, which can then be used in the production of healthy foods, nutraceuticals and pharmaceuticals [17,19,20,38].…”
Section: Current Food Applications Of Ancient Grainsmentioning
confidence: 99%
“…Ancient grains cause fewer allergic reactions and are also more tolerable than normal grains for FODMAP diet foods [49]. Some ancient grains are rich sources of resistant and slowly digestible starch, which can be used for the production of low GI and low-calorie foods suitable for weight control and diabetes [13,15]. They can be used as a source of plant protein required in meat-free diets and also in countries where access to other protein sources is limited.…”
Section: Ancient Grains For Special Diet Foodsmentioning
confidence: 99%
“…In terms of protein content, it is higher in ancient cultivars than in modern ones; at the same time, the gluten content is also higher, but the quality is completely different with much weaker structure and strength [12]. A preliminary in vitro and in vivo study suggested that ancient grain varieties are better tolerated by people with non-celiac wheat sensitivity and irritable bowel syndrome, resulting in a longer diagnostic delay than modern grains [15].…”
Section: Introductionmentioning
confidence: 99%